2005
DOI: 10.2298/vsp0501039b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori in gastric biopsy and resection specimens

Abstract: Immunohistochemical identification of H. pylori was better than Giemsa stain for detecting that organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In relevance with this, in the present study, the low socio economic group (93%) was observed to be more susceptible to Helicobacter pylori infection. Javed et al [14] also states that the rate of Helicobacter pylori infection is directly propotional to age with a maximum number seen in the age group of 46-55yrs. In the age group of 41-50 years, the maximum occurrence of Helicobacter pylori associated gastritis was noted (Adisa et al [15]).…”
Section: Discussionmentioning
confidence: 99%
“…In relevance with this, in the present study, the low socio economic group (93%) was observed to be more susceptible to Helicobacter pylori infection. Javed et al [14] also states that the rate of Helicobacter pylori infection is directly propotional to age with a maximum number seen in the age group of 46-55yrs. In the age group of 41-50 years, the maximum occurrence of Helicobacter pylori associated gastritis was noted (Adisa et al [15]).…”
Section: Discussionmentioning
confidence: 99%